Bijnkershoek over de 'Quade Conduites' van Huibert Rosenboom, President van de Hoge Raad (1691-1722): Een Bijdrage op Grond van tot Dusverre Onuitgegeven Teksten uit de Observationes Tumultuariae (als Bijlage Toegevoegd) - Sirks, A (2008)
The volumes of the manuscript of the Observationes tumultuariae of Cornelis van Bijnkershoek (1673-1743) contain loose leaves and endleaves with notes by his hand. Some of these notes, in particular those on the endleaves of volumes IX-XIV, have already been published. Among the unpublished notes, Bijnkershoek's observations on malpractices of President Rosenboom and his fellow judges in the Supreme Court of the provinces of Holland and Zeeland are of special interest: they constitute the basis of the present article. In an appendix the text of these observations is published together with the full text of the endleaves of volumes I-VIII, concerning other everyday matters of the Court. © 2008 Martinus Nijhoff Publishers.